Student resistance to active learning: do instructors (mostly) get it wrong?. Issue 2 (2nd July 2020) - Andrews, Madison E.; Graham, Matthew; Prince, Michael; Borrego, Maura; Finelli, Cynthia J.; Husman, Jenefer
ABSTRACT: Adopting evidence-based teaching practices, such as active learning, has proven to increase student learning, engagement, and interest in STEM and subsequently, the number and diversity of STEM graduates. Despite these compelling findings, the translation of educational research to classrooms has been slow, in part due to instructors' concerns about student resistance. To better understand STEM instructors' and students' attitudes and behaviours regarding active learning, we administered surveys to instructors and their students and conducted classroom observations. The instructor survey measured their attitudes towards & use of active learning, strategies used to reduce student resistance, and perceptions of student behaviour. The corresponding student survey asked students to evaluate their instructors' teaching practices, as well as students' own attitudes and behaviours during class that day. Classroom observations supplemented these metrics. Analyses of matched survey datasets (n = 27, n = 758) and observations (n = 13) reveal a disconnect between instructor perceptions of their students' responses to active learning and students' self-reported attitudes and behaviours, where instructors overestimate student resistance. In contrast, students report they see value in the activities, enjoy them, and even plan to highly evaluate the course and instructor. Overall, these results suggest that instructors' fears about adopting these teaching practices are largely erroneous.